The Bobwhite Quail Initiative: Restoring Georgia's State Gamebird While Improving the Environment (Poster Abstract) - Chris Baumann; Bobby Bond; Joy Bornhoeft; John Carroll; Adam Hammond (National Quail Symposium Proceedings, 2017)
Like many southeastern states, Georgia’s northern bobwhite (Colinus virginianus) population has declined by more than 70% since the 1960s. Research has indicated that the primary cause of this decline is the reduction in habitat quality resulting from intensification of agriculture and forestry practices. To address this problem, members of Georgia’s General Assembly worked with the Department of Natural Resources Wildlife Resources Division (WRD) and other conservation organizations to develop and fund the Bobwhite Quail Initiative (BQI) during the 1999 legislative session. The BQI was designed to restore habitat for bobwhites, songbirds, and other farm wildlife on private lands, and was implemented in 14 counties in Georgia (subsequently expanded to 17 in 2000). In the first year of the program, BQI personnel provided technical assistance for > 100,000 acres of land allocating > 51,000 to enroll landowners for the first contract period (2000–2002) of the BQI. Although Georgia incurred extreme drought during the summer of 2000, bobwhite quail and songbird response to BQI management practices during the first season of the program indicated that these practices had positive impacts on both. Bobwhite populations remained stable or increased on 71% of the treatment farms, while 75% of the control farms experienced population declines. Sparrow species dependent upon early successional habitat also increased by 30% in managed fields of BQI.